Aerobic Bacteria and Antibiotic Sensitivity on Odontectomy Wound in RSUD Arifin Achmad Riau - Rita Endriani; Elita Rafni; Agung Prakoso; Farhan Hadi; Vezi Dwideta; Azzahra Alni (International Journal of Scientific Research in Dental and Medical Sciences, 2022)
Background and aim: The impacted tooth is defined as a condition where the tooth fails to erupt into the dental arch. It could be extracted with a procedure called odontectomy. The most common complication of this procedure is infection by aerobic as well as anaerobic bacteria, and antibiotics could treat this complication. This study aimed to identify the type of bacteria found on the wound of odontectomy patients and the antibiotics sensitivity pattern in RSUD Arifin Achmad Riau. Material and methods: Patient specimens after odontectomy were collected from wound swabs. All specimens were then cultured and identified for the type of bacteria, and an antibiotic sensitivity test was done by Kirby-Bauer method according to the Clinical and Laboratory Standard Institute (CLSI). Results: This study found that the most dominant population patient odontectomy is female (66.67%), 15-55 years old, graduated from senior high school (63.33%), the third molar as the affected tooth (86.67%), and located in the lower jaw (100%). Gram-positive bacteria (52%) followed by Alpha-hemolytic Streptococcus (40.74%), Staphylococcus aureus .22,22%) and Coagulase Negative Staphylococci (37.04%). Gram-negative bacteria (48%) followed by Klebsiella sp. (56%), Enterobacter sp. (32%), Pseudomonas sp. (8%), and Escherichia coli (4%). The antibiotics with the highest sensitivity were levofloxacin, meropenem, chloramphenicol, gentamicin, sulphamethoxazole, amikacin, ceftazidime, fosfomycin, and ciprofloxacin. All bacteria were resistant to ampicillin and metronidazole. Conclusions: Klebsiella sp and Alpha-hemolytic Streptococcus are the most dominant bacteria found in the wound of odontectomy patients. Antibiotics recommended for post-odontectomy wounds are Carbapenem and Quinolones.